Factors Affecting of Small Business Operators in Luang Prabang City - Lattanakone, Phetvanpheng; Hoongsengpha, Soudthida; Sengchan, Souksamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aims to study the level of operational capability and the relationship between the factors affecting small business operators in Luang Prabang City. The sample for this research was the small businesses (SMEs) in Luang Prabang City (198 total). Using the five levels of the Likert Scale of the questionnaire to collect data, there is a reliability level of 0.907 (90.7%), and Using SPSS statistical software, the data are analyzed by frequency, percent, mean, standard Deviation, Pearson Correlation coefficient, and Multiple Regression Analysis. The result of the research found that the capacity for operation of small businesses in Luang Prabang City appears to be at its highest level. Among them, the operation of small businesses in Luang Prabang City has the highest level in terms of production, service, and management. Then the financial and marketing aspects are at a good level, and the ability factors of small businesses that have a linear relationship and have the same effect and result in the operation of small businesses in Luang Prabang city include three factors: Competitive Aggressiveness, innovation, and Autonomy of Internal factors. While the External factor has a linear relationship, it has the same result as the economic factor that affects the operation of small businesses in Luang Prabang.